2016
DOI: 10.1055/s-0036-1593851
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Presepsin in Detection of Early-Onset Neonatal Sepsis

Abstract: The aim of this study was to evaluate the efficacy of presepsin in both diagnosis and follow-up of early-onset neonatal sepsis (EOS) and also to compare its effectiveness with C-reactive protein (CRP) and procalcitonin (PCT). A total of 29 term infants with EOS group and 40 term infants with control group were included in this study. Before initiating therapy, blood samples for whole blood count, CRP, PCT, presepsin, and culture were obtained from all neonates (T0). This procedure was repeated two times at 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
1
30
0
4
Order By: Relevance
“…Presepsin has a higher sensibility and specificity in neonatal sepsis, compared to CRP and PCT. c similar to the value stated in other recent studies regarding early onset sepsis in term/ preterm newborns [25,26]. Higher PSP cutoff values, found in other studies, are in relation with the chronological age when the sample was taken.…”
Section: Resultssupporting
confidence: 87%
“…Presepsin has a higher sensibility and specificity in neonatal sepsis, compared to CRP and PCT. c similar to the value stated in other recent studies regarding early onset sepsis in term/ preterm newborns [25,26]. Higher PSP cutoff values, found in other studies, are in relation with the chronological age when the sample was taken.…”
Section: Resultssupporting
confidence: 87%
“…However, due to the lack of information about presepsin reference range in neonates, many studies reported different cut-off values 22,25,26. Relatively different cut-off values may be due to the use of different measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, its disadvantage is that it is easily affected by the subjective factors of the scorer when the neonate's score is low, often leading to inaccurate results. Besides, the Apgar score is vulnerable to other neonatal diseases, lacking specificity in the judgement (23). In this study, the changes in blood gas indexes and acid-base balance in patients with pregnancy-induced hypertension syndrome were detected, combined with the neonate's Apgar score, which could make countermeasures against neonatal asphyxia during delivery in advance.…”
Section: Discussionmentioning
confidence: 99%